Analisis Smash Cut Dalam Memperkuat Unsur Dramatik Pada Film Asteroid City Karya Wes Anderson - Ahmad Haryadi (Cinelook: Journal of Film, Television, and New Media, 2025)
This study analyzes how the Smash Cut editing technique strengthens the dramatic elements, particularly Surprise, in Wes Anderson's film Asteroid City (2023). This research uses a qualitative method with a visual analysis approach to dissect the film's editing structure. The study identifies and analyzes 10 key scenes where smash cuts are strategically implemented. The findings reveal that the Smash Cut technique effectively creates surprise by generating abrupt and sharp contrasts in audio visual elements, scene atmosphere, and narrative flow. These transitions, from loud, chaotic scenes to silent, contemplative ones, or from public joy to private tension, deliberately break the audience's expectations. The application of this technique aligns with film editing theories from Gael Chandler, who defines its function as a tool to shock the audience; Bruce Block, on using visual contrast to generate emotional impact, and Walter Murch's Rule of Six, which prioritizes emotion and story over simple visual continuity. The research concludes that in Asteroid City, the Smash Cut is not merely a stylistic choice but a calculated narrative device used to control rhythm, intensify the dramatic experience, and amplify the element of Surprise.